Antioxidant Activities of the Leaf Extract and Fractions of Dryopteris filix-mas (L.) Schott could be Attributed to The Abundance of Polyphenol Compounds - Earnest Oghenesuvwe Erhirhie; Emmanuel Emeka Ilodigwe; Daniel Lotanna Ajaghaku; Blessing Ogechukwu Umeokoli; Peter Maduabuchi Eze; Festus Basden Chiedu Okoye (Biology, Medicine, & Natural Product Chemistry, 2020)
Dryopteris filix mas (D filix-mas) is wildly used in ethnomedicine for the management of rheumatoid arthritis, wounds and other diseases. We investigated the anti-oxidant activities of its leaf extract, and chromatographic fractions. The ethanol leaf extract was partitioned into four fractions; n-hexane, ethyl acetate, n-butanol and water. Ferric reducing anti-oxidant power (FRAP), 1, 1-diphenyl-2-picrylhydrazil (DPPH) and nitric oxide (NO) scavenging in vitro assays were carried out on the extract and fractions at 6.25, 12.5, 25, 50, 100, 200, 400 and 800 µg/mL. The most active fraction (ethyl acetate fraction) was further purified using chromatographic techniques to isolate its major compound whose structure was elucidated using ID nuclear magnetic resonance (NMR) and mass spectrometry. The ethyl acetate fraction produced the highest free radical scavenging activity among the other fractions. The fraction (VLC-E7) from which the bioactive compound, quercetin-3-O-αL-rhamnopyranoside, was isolated had the best FRAP and DPPH scavenging activities with EC50 and IC50 values of 88.81 ± 3.41 and 26.87 ± 0.24 respectively more than the ethyl acetate fraction. This study revealed that the polyphenol flavonoid, quercetin-3-O-αL-rhamnopyranoside could be responsible for antioxidant activity of ethno-medicinal property of D filix-mas leaf.